2021
DOI: 10.1111/cge.13947
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular classes and growth hormone treatment on growth and dysmorphology in Prader‐Willi syndrome: A multicenter study

Abstract: Prader‐Willi syndrome (PWS) is a complex genetic disorder with three molecular classes but clinical ascertainment is based on distinctive features. The prevalence of dysmorphic features was studied in 355 PWS participants (61% deletion, 36% maternal disomy [UPD], and 3% imprinting defects) from the National Institute of Health PWS Rare Diseases Clinical Research Network. The effect of growth hormone (GH) treatment on growth and dysmorphic features was compared. Among participants, upslanting palpebral fissures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Weight and BMI were higher in the DEL 15 group, which suggests that these patients are more prone to obesity [ 35 ]. These results correspond with the findings by Mahmoud and Leonenko et al in a multicentre study of a large cohort of 355 patients, published this year [ 36 ]. However, the authors of the above studies did not analyse the characteristics of patients with PWS with a different molecular diagnosis at the start of rhGH therapy.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Weight and BMI were higher in the DEL 15 group, which suggests that these patients are more prone to obesity [ 35 ]. These results correspond with the findings by Mahmoud and Leonenko et al in a multicentre study of a large cohort of 355 patients, published this year [ 36 ]. However, the authors of the above studies did not analyse the characteristics of patients with PWS with a different molecular diagnosis at the start of rhGH therapy.…”
Section: Introductionsupporting
confidence: 92%
“…It may be also speculated that the clinical, mainly dysmorphic features of PWS, other than short stature or higher BMI, are more relevant in the children with DEL 15. The DEL 15 phenotype has been described as a classic PWS phenotype that may therefore lead to the earlier diagnosis and start of the therapy [ 28 , 36 ]. The evident difference between the birth length SDS and height SDS before the start of the treatment in our research, independent of the genetic subtype, may indicate that there is a significant decrease in postnatal growth in children with PWS, regardless the specific molecular diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports of strabismus among individuals with PWS range from 28 to 95 % [ 11 ]. Most recently, a clinical study of the effect of growth hormone therapy on 355 PWS participants reported a strabismus prevalence of 42 %, which is line with the results reported here [ 17 ]. That study also showed a statistically higher prevalence of strabismus in individual with PWS by UPD versus those with the deletion subtype (53 % vs. 39 %) [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Most recently, a clinical study of the effect of growth hormone therapy on 355 PWS participants reported a strabismus prevalence of 42 %, which is line with the results reported here [ 17 ]. That study also showed a statistically higher prevalence of strabismus in individual with PWS by UPD versus those with the deletion subtype (53 % vs. 39 %) [ 17 ]. The current study of data from the Global PWS Registry, with almost 3 times the number of subjects, did not confirm this suggested difference in prevalence of strabismus by genetic subtype.…”
Section: Discussionsupporting
confidence: 91%